Toward smallholder bamboo-integrated agro-silvopastoral systems in sub-Saharan Africa: assessing the impact of bamboo leaves on consumption pattern, growth performance and manure characteristics of West African dwarf goats - Sasu, Prince; Attoh-Kotoku, Victoria; Anim-Jnr, Antoinette S.; Kwaku, Michael; Adjei-Mensah, Benjamin; Adjei, Obed; Mintah, Frank Kweku (Frontiers in Animal Science, 2023)
In a 30-day study, the feed intake, growth performance, and manure characteristics of West African dwarf goats (WAD) were evaluated. The study involved a total of 30 animals with an average live weight of 9.9 ± 0.21 kg. These animals were divided into a control group and four test groups using a 2 x 2 factorial arrangement within a completely randomised design (CRD). Each treatment consisted of six replicates with five dietary treatments as follows: T1 (control): Basal diet composed of 60% Megathyrsus maximus and 40% Bridelia ferruginea leaves. T2: Basal diet of T1 supplemented with 400 g/day of Oxytenanthera abyssinica (A. Rich.) Munro leaves. T3: Basal diet of T1 supplemented with 400 g/day of Bambusa balcooa (Beema) leaves. T4: Basal diet of T1 supplemented with 600 g/day of O. abyssinica (A. Rich.) leaves. T5: Basal diet of T1 supplemented with 600 g/day of B. balcooa leaves. The data were analysed using Generalised Linear Model Procedures in Minitab Statistical Software at a 5% significance level. The results showed varied (p < 0.05) chemical compositions among the feed constituents, spanning from 53 to 194 gkg-1 DM for crude protein, 8 to 22 gkg-1 DM for nitrogen, 844 to 911 gkg-1 DM for organic matter, and 88 to 155 gkg-1 DM for ash. In terms of quality, the O. abyssinica supplement generally outperformed the B. balcooa supplement. Parameters such as daily feed intake, average daily gain, and feed conversion efficiency showed a range of 398 to 469 g/day, 27 to 72 g/day, and 1 to 15%, respectively. Comparatively, higher daily dry matter intake was recorded for the animal groups fed B. balcooa supplement than their counterparts fed the O. abyssinica supplement. However, the O. abyssinica groups were more efficient in converting feed to body weight, . Furthermore, the animal group that received a daily supplement of 400 g gave higher efficiency, with performance approximately 3.2% higher compared to the group receiving 600 g. To conclude, integrating 400 grams of bamboo leaves into the diet can enhance basal diet consumption, accelerate animal growth, and yield manure akin to chemical fertilizers